Impact of HCMV Infection on NK Cell Development and Function after HSCT - Della Chiesa, Mariella; Falco, Michela; Muccio, Letizia; Bertaina, Alice; Locatelli, Franco; Moretta, Alessandro (Frontiers in Immunology, 2013)
Natural Killer (NK) cell function is regulated by an array of inhibitory and activating surface receptors that during NK cell differentiation, at variance with T and B cells, do not require genetic rearrangement. Importantly, NK cells are the first lymphocyte population recovering after hematopoietic stem cell transplantation (HSCT). Thus, their role in early immunity after HSCT is considered crucial, as they can importantly contribute to protect the host from tumor recurrence and viral infections before T-cell immunity is fully recovered. In order to acquire effector functions and regulatory receptors, NK cell precursors undergo a maturation process that can be analysed during immune reconstitution after HSCT. In this context, the occurrence of human cytomegalovirus (HCMV) infection/reactivation was shown to accelerate NK cell maturation by promoting the differentiation of high frequencies of NK cells characterized by a KIR+NKG2A− and NKG2C+ mature phenotype. Thus, it appears that the development of NK cells and the distribution of NK cell receptors can be deeply influenced by HCMV infection. Moreover, in HCMV-infected subjects the emergence of so called “memory-like” or “long-lived” NK cells has been documented. These cells could play an important role in protecting from infections and maybe from relapse in patients transplanted for leukemia. All the aspects regarding the influence of HCMV infection on NK cell development will be discussed.